Moving memories: Stories of the Tina Martins shelter in the fight against gender violence - Thaís Zimovski Garcia de Oliveira; Rafael Diogo Pereira; Alexandre de Pádua Carrieri; Gabriel Farias Alves Correia (RAE: Revista de Administração de Empresas, 2021)
This article presents different stories and memories of the Tina Martins Women’s Referral Center. To this end, we moved away from the qualitative studies of history and memory in organizational studies that are based on the historic turn, which aims to go beyond the production of narratives that resort to the past as a tool for reproducing the power relations of the present. A vast amount of material was compiled from observing participants, including a field notebook, event records, and photographs, and individual interviews were recorded and transcribed. The results were organized into two main thematic axes: the first presents the process that led to the Center’s foundation and the political disputes over its space, while the second addresses the meanings present in the group’s everyday life. Given the construction of diversified and procedural historical narratives, this article proposes some critical reflections on the Center’s experience that were discussed with its members, and instigates, via memories, the adoption of the historical approach to organizational studies.